PARENTS' DECISIONS IN CHOOSING K-12 EDUCATION DURING THE COVID-19 PANDEMIC: AN EXPLORATORY FACTOR ANALYSIS - Harianto, Eric; Tambunan, Damelina; Dewi, Liliana; Dinata, Yuwono Marta (Universitas Brawijaya, Indonesia, 2022)
The Covid-19 pandemic has had a major impact on K-12 schools. Therefore it is very important to examine the factors that shape parents' decisions in choosing K-12 education for their children so that schools can meet parents' expectations. As a result, student enrolment in K-12 schools can be increased. This study aims to determine the factors that shape parents' decisions in choosing kindergarten, elementary, junior high, and high school (K-12) education levels for their children in the new normal era. The object of research is the Citra Blessing School in Surabaya. The method used is a quantitative research method. Data collection in this study using questionnaire research. The population is 1,142 parents from K-12. Sampling using a random sampling technique. 797 parents were used as the sample. The analytical method used is exploratory factor analysis (EFA) with the help of the SPSS application. As a result, there is 1 factor that is not appropriate from the 27 initial factors, so 26 factors are used as a factor for parents' decision-making in choosing K-12 education. These 26 factors form 4 new factors, namely 1. Service and Ambience Excellence; 2. Student Competence; 3. Learning Management System, and 4. School Reputation. This finding becomes a reference for improving the performance of K-12 in Surabaya. In particular, so that the quality of education, the quality of alumni, student admissions, and student enrolment can be improved. It is in order to maintain the continuity of schools, especially K12 schools in the New Normal period. It is a reference for K-12 students to use flip classrooms or blended learning as learning methods during the teaching and learning process. In addition, it motivates K-12 to take part in competitions, thereby increasing the school's academic achievement.